On the Convention of Medical Commitment in the Perspective of the Eastern Syrian Apostolic Documents - ZHU, Donghua (Journal of Research for Christianity in China (JRCC), 2022)
In the Middle Ages in Eurasia, there was an economic and cultural network built along the Silk Road, among which Nestorian Christianity were undoubtedly one of the more active groups with greater contribution. Chinese and foreign scholars have long noticed the characteristics of Nestorian party by their medical service, medical team and medical quality. In the process of deeply participating in the construction of the community with a shared future along the Silk Road, their medical activities are undoubtedly a very important part. It is precisely because of their dedication to upholding medical enterprise and being good at medicine that the medical teams of Nestorian Christianity have won respect and support from people in their society. Therefore, they have also made many achievements and made their own unique contributions to the construction of a community of shared future in which diversity is compatible, adversity is shared and weal and woe is shared. This paper aims to outline various manifestations of the Nestorian tradition of medicine, and on the basis of interpreting the Eastern Syrian apostolic documents, explore the characteristics, connotation and ideological basis of the Nestorian concept of medicine, so as to clarify the basis for the formation of the Nestorian tradition of medicine.